“The orphaned fervour”... Or: the truth of knowledge - Bartlett, A.J. (Filozofski vestnik, 2017)
Plato’s Apology stages a scene reminiscent of Lacan’s impromptu at Vincennes whereat Lacan famously tells the protesting students that the “regime is putting you on display,” saying “look at them enjoying.” The effect, he says, will be to deliver yourselves over to the master, once again. In Plato’s case, three figures Meletus, Anytus and Lycon, representing respectively, the poets-teachers, businessmen-politicians and orators of the law and thus the state as such ¬ accuse Socrates of failing to enjoy in the prescribed way. Socrates is accused of harbouring and of practicing an impossible desire for thought. To think is to corrupt; to pass through enjoyment as its radical impossibility. Plato’s entire problematic in the dialogues, exemplified in the Apology, is to think the question of educational corruption against these ubiquitous and determinative performances of pedagogical enjoyment. This essay stages these several points and connections and draws some consequences for the thought of education today.